PELAKSANAAN PROGRAM PELATIHAN DAN PENGEMBANGAN KARYAWAN FRONT OFFICE DI HOTEL FURAYA KOTA PEKANBARU - Fitria A; Lilis Suriani (VALUTA, 2015)
Employee training and development programs implemented in order to reduce oreliminate the gap between the ability of employees to the desired organization, that is byincreasing knowledge and skills and change attitudes. But" How Implementation ofEmployee Training and Development in Hotel Front Office FurayaPekanbaru ?" Fromthis study the authors hope to be an alternative as well as considerations in employeetraining and development programs . The purpose of this study is to identify andanalyze the implementation of employee training and development programsparticularly Front Office employee at Hotel FurayaPekanbaru. To determine the factorsthat affect the implementation of employee training and development programs in HotelFront Office FurayaPekanbaru. The number of samples in the Front Office employeesas many as 17 samples . In sampling the authors use the census the total population ofthe sampled population is small and because the amount of easily accessible byresearchers, the primary data is a source of data that was obtained directly fromrespondents through interviews, questionnaires (questionnaires) and observations, suchas the identity of respondents and respondents about how the Implementation ofEmployee Training and Development in Hotel Front Office FurayaPekanbaru, whilesecondary data is a source of data and information as well as information from theparties relating to this study. To obtain the data and information that is more valid, datacollection techniques used were questionnaires, observation, and interviews. Thisresearch survey form explanation is research that takes a sample of the population andthe use of questionnaires as the main data collection tool, so that the data is expected toanswer the research desired. From these results it can be concluded that the ProgramImplementation Training and Employee Development Front Office at HotelPekanbaruFuraya works quite well. However it is suggested to be increased in thefuture in order for the company nor the employee in order to carry out the training anddevelopment of more effective.